The impact of the application of Islamic accounting standards (AAOIFI) on the financial performance of Islamic banks operating in the Kurdistan Region of Iraq - Mohammed, Kasar; Younes, Nader (Humanities Journal of University of Zakho, 2023)
The current research reviews the effect of applying Islamic accounting standards on the financial performance of Islamic banks in the presence of the Central Bank of Iraq’s instructions, which obligate Islamic banks to apply the standards issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), after Iraq joined The purpose of this research is to analyze the annual consolidated financial statements of Islamic banks operating in the Kurdistan Region of Iraq during the period (2015-2020), to find out whether these banks are committed to applying these standards after joining the Accounting and Auditing Organization for Islamic Financial Institutions and the impact of applying these Standards on the financial performance of these banks. In order to achieve this, we analyzed the financial statements of Islamic banks, the research sample, during the research period, and then we analyzed the financial performance based on the rate of return on assets indicator to measure the financial performance, as well as conducting an analysis (Z-Scoring Kida) to measure the financial failure of those banks. The researchers found that the instructions of the Central Bank of Iraq are more effective in controlling Islamic banks whose main centers are in Baghdad compared to Islamic banks whose main centers are in the region. Standards, and this indicates a defect in the actual application of these standards, which led to their ineffectiveness in raising the level of financial performance of Islamic banks.